Pengaruh Penggunaan Information System Terhadap Competitive Advantage Melalui Intellectual Capital Pada Industri Perhotelan Di Jawa Timur - Kevin Setiadi; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct and significant affect of Information System to Intellectual Capital; Intellectual Capital to Competitive Advantage; and Information System to Competitive Advantage in hospitality industries in East Java. This study also examine the indirect and significant relationship of Information System to Competitive Advantage through Intellectual Capital as intervening variable in hospitality industries in East Java. This study used a quantitative approach, and the data were obtained by distributing questionnaires to hospitality industries in East Java and processed by using smartPLS software. This study showed that there was positive and significant relationship of Information System to Intellectual Capital; Intellectual Capital to Competitive Advantage; and Information System to Competitive Advantage in hospitality industries in East Java. But, Intellectual Capital was inadequate to become as intervening variable between Information System and Competitive Advantage because the direct relationship between Information System and Competitive Advantage gave greater affect than if it was through Intellectual Capital.